Dynamic sensitivity to resource availability influences population responses to mismatches in a shorebird. Issue 9 (12th June 2022) - Wilde, Luke R.; Simmons, Josiah E.; Swift, Rose J.; Senner, Nathan R.
Abstract: Climate change has caused shifts in seasonally recurring biological events leading to the temporal decoupling of consumer–resource pairs, that is, phenological mismatching. Although mismatches often affect individual fitness, they do not invariably scale up to affect populations, making it difficult to assess the risk they pose. Individual variation may contribute to this inconsistency, with changes in resource availability and consumer needs leading mismatches to have different outcomes over time. Nevertheless, most models estimate a consumer's match from a single time point, potentially obscuring when mismatches matter to populations. We analyzed how the effects of mismatches varied over time by studying precocial Hudsonian godwit ( Limosa haemastica ) chicks and their invertebrate prey from 2009 to 2019. We developed individual‐ and population‐level models to determine how age‐specific variation affects the relationship between godwits and resource availability. We found that periods with abundant resources led to higher growth and survival of godwit chicks, but also that chick survival was increasingly related to the availability of larger prey as chicks aged. At the population level, estimates of mismatches using age‐structured consumer demand explained more variation in annual godwit fledging rates than more commonly used alternatives. Our study suggests that modeling the effects of mismatches as the disrupted interaction between dynamic consumer needs and resource availability clarifies when mismatches matter to both individuals and populations.